Temperature Trends and Change Points in Iraq - Dr. Ahmed Lafta Hamad Al-Budeiri (Journal of College of Education, 2025)
This study provides a temporal and spatial analysis of trends in maximum and minimum temperatures in Iraq during the period (1950-2022) (73 years) for twelve stations representing various regions of the country, based on data from the Climate Research Unit (CRU TS v4.07). The study employs the Mann-Kendall test to assess the statistical significance of trends, Sen’s method to estimate the rate of change, and the Taylor test to identify change points.The findings reveal a significant increasing trend in both maximum and minimum temperatures, with an annual change rate ranging between 1.8 – 1.9°C per century. Seasonal variations were more pronounced in summer and spring, particularly in the southern regions, where the change in minimum temperatures ranged between 0.38 – 0.43°C per decade, indicating that minimum temperatures are more affected by climate change.Iraq has experienced statistically significant change points across all stations, particularly in the 1990s, with 75% of the stations showing change points in 1994, aligning with global trends. These climatic shifts are expected to exacerbate economic and environmental pressures, particularly in agricultural production, water resource management, and energy consumption.Thus, it is crucial to adopt effective future policies and strategies to adapt to climate change and mitigate its negative impacts.
Keywords: Climate change, Change points, Temperature, Trend, Iraq.